The Early Prognosis Value of Activin A in Premature Infants’ Brain Injury - Shahid, Ahmad Daniyal; Zhu, Haitao; Lu, Hong Yan; Chang, Ming; Malik, Abdul; Sher, Murad Ali; Adil, Walid Ullah (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2017)
The purpose of this research is to explore the predictive value of amniotic fluid, umbilical cord blood and neonatal blood activin A in early brain injury in preterm neonates. 98 cases of premature infants were divided into brain injury group and control group according to the cranial imaging examination, and the brain injury group was further divided into mild brain injury group and severe brain injury group. The activin A level was measured in both preterm brain injury group and control group with enzyme-linked immunosorbent assay (ELISA) kit, then the comparisons of activin A levels between brain injury group and control group, mild and severe brain injury group were implemented to find out their differences. The results demonstrated that activin A levels of umbilical cord blood, amniotic fluid and 3-day-old premature infant peripheral blood in brain injury group were significantly higher than the control group (P<0.05), activin A levels of amniotic fluid, umbilical cord blood and 3-day-old infant blood in the severe brain injury group were significantly higher than the mild brain injury group (P<0.05), intragroup comparison among the brain injury group showed amniotic fluid and 3-day-old premature infant serum activin A levels were significantly higher than umbilical cord blood (P<0.05), activin A has a certain value in early prediction and severity assessment of preterm brain injury.